(3OaY eVGQ GdCHOGf HCQV eUQs - (3Ydj Hf QVhGf Hf Ydj Hf LYaQ, CHh GdMSf,J (B453 (3g` s
(3ChdgG (B:s
(3CeG HYO (B: (3gPG cJGH Ydi Hf QVhGf , ai OaY eVGQ GdGHOGf HeUQ bGd Ydi Hf QVhGf (B: (3bUOfG Cf fdNU GdMjdI s
(3BNQgG (B:s
(3aCgd eUQ EPf CaVd CNdGbkG hCLhO WQjbI , hQSeJ gPG gGgfG djdMb HeG JbOe Ef TGA Gddg YR hLd s
(3QJHg Ydi NeSI YTQ aUdkGs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B289 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B94s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B474 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B87 s
Keywords: (3GdWHs